2013
DOI: 10.1093/pcp/pct151
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Environmental Responses of PATROL1 in Arabidopsis Subsidiary Cells

Abstract: The Arabidopsis stomatal complex is composed of a pair of guard cells and surrounding anisocytic subsidiary cells. Subsidiary cells are thought to function as a supplier and receiver of bulk water and ions, and to assist turgor-driven stomatal movement, but the molecular mechanisms are largely unknown. In this work, we studied the dynamic behavior and environmental responses of PATROL1, which has been identified as a translocation factor of the plasma membrane proton pump ATPase (PM H(+)-ATPase) AHA1 in guard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 15 publications
4
37
0
Order By: Relevance
“…() hypothesized that the anomalous stomata clustering could prevent the proper functioning of closely spaced guard cells and limit full opening of stomata apertures. The functioning of guard cells’ complex opening mechanism, including ion transport across channels between guard cell and neighboring subsidiary cells (Pandey et al ., ; Kim et al ., ; Higaki et al ., ), may be impaired by disrupting signaling and suppressing formation of specific membrane proteins (Klein et al ., ), and by mechanical limitation to volume change of the guard cell (Franks & Farquhar, ). Franks & Farquhar () have shown experimentally for grass‐type stomata that the maximum aperture of stomatal pore requiring greater lateral displacement of guard cells is inhibited for full epidermis (subsidiary) cells and that the effective aperture was only c .…”
Section: Resultsmentioning
confidence: 99%
“…() hypothesized that the anomalous stomata clustering could prevent the proper functioning of closely spaced guard cells and limit full opening of stomata apertures. The functioning of guard cells’ complex opening mechanism, including ion transport across channels between guard cell and neighboring subsidiary cells (Pandey et al ., ; Kim et al ., ; Higaki et al ., ), may be impaired by disrupting signaling and suppressing formation of specific membrane proteins (Klein et al ., ), and by mechanical limitation to volume change of the guard cell (Franks & Farquhar, ). Franks & Farquhar () have shown experimentally for grass‐type stomata that the maximum aperture of stomatal pore requiring greater lateral displacement of guard cells is inhibited for full epidermis (subsidiary) cells and that the effective aperture was only c .…”
Section: Resultsmentioning
confidence: 99%
“…Studies using dominant negative and mutant approaches showed that SYP121 and SYP122 do not affect plasma membrane H + -ATPase traffic (Geelen et al, 2002;Sutter et al, 2006). Indeed, the SNARE regulatory protein, PATROL1, which is known to affect H + -ATPase traffic, does not associate with SYP121 and SYP122 (Higaki et al, 2014). Thus, multiple lines of evidence discount any role of these two major Qa-SNAREs in H + -ATPase traffic.…”
mentioning
confidence: 99%
“…Previously, Higaki et al (2014) found that 20 μM LY294002 did not perturb the appearance of GFP-PATROL1 dots, whereas the GFP-PATROL1 dots disappeared with 20 μM PAO treatment. In this study, 20 μM LY294002 did not affect stomatal closure in response to CO 2 , darkness, and ABA (Supplementary Figure S2 nor the activity of GFP-PATROL1.…”
Section: Discussionmentioning
confidence: 88%